2018
DOI: 10.3390/nu10050569
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Study on the Safety and Efficacy of Daily Ingestion of Green Tea (Camellia sinensis L.) cv. “Yabukita” and “Sunrouge” on Eyestrain and Blood Pressure in Healthy Adults

Abstract: The green tea (Camellia sinensis L.) cultivar “Sunrouge” contains anthocyanins, catechins and flavonols. To determine whether ingesting green tea containing anthocyanins improves visual function and blood pressure (BP) in healthy adults, a randomized, double-blind, placebo-controlled study was performed. A total of 120 healthy subjects, aged between 20 and 60 years and with a systolic BP (SBP) value of ≤125 and <155 and a diastolic BP (DBP) value <95, or a DBP of ≤75 mmHg and <95 mmHg and a SBP <155 mmHg, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The results of this study showed no significant BP or visual improvement in the “Yubukita” group. Moreover, the “Sunrouge” group showed an increase in blood pressure (SBP of 123.3 ± 12.9 mmHg at baseline, compared to 129.8 ± 12.7 mmHg after 12 weeks, p < 0.01 and DBP of 77.1 ± 8.5 mmHg at baseline, compared to 82.4 ± 8.2 mmHg after 12 weeks, p < 0.01) at bedtime, as well as improvement of the eye accommodation ability in subjects below the age of 45 [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study showed no significant BP or visual improvement in the “Yubukita” group. Moreover, the “Sunrouge” group showed an increase in blood pressure (SBP of 123.3 ± 12.9 mmHg at baseline, compared to 129.8 ± 12.7 mmHg after 12 weeks, p < 0.01 and DBP of 77.1 ± 8.5 mmHg at baseline, compared to 82.4 ± 8.2 mmHg after 12 weeks, p < 0.01) at bedtime, as well as improvement of the eye accommodation ability in subjects below the age of 45 [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, flavonoids from tea catechin were effective for increasing serum adiponectin levels, and dietary supplements rather than whole foods intervention were effective in increasing adiponectin levels. Although existing evidence from RCTs suggests that flavonoid intervention could elevate adiponectin levels (Bell et al, 2011; Hussain et al, 2017; Maeda‐Yamamoto et al, 2018), there is evidence of null effects (Brull et al, 2017; Hsu, Liao, Lin, Tsai, Huang, & Chou, 2011; Liu et al, 2014). Our meta‐analysis suggests that flavonoids with an intervention duration longer than 12 weeks might be required to observe the improved effects on adiponectin post‐flavonoid intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from human randomized controlled trials (RCTs) are controversial with regard to the effects of flavonoid intake on circulating adiponectin and leptin levels. On the one hand, evidence suggests that flavonoid intervention could elevate adiponectin levels (Bell, Canale, & Bloomer, 2011; Capomolla et al, 2019; Huang, Liu, Wang, Huang, & Hsu, 2018; Hussain, Habib Ur, & Akhtar, 2017; Maeda‐Yamamoto et al, 2018) and/or reduce leptin levels (Kani et al, 2017; Lee, Cha, Lee, & Yim, 2016; Wu et al, 2005); on the other hand, there are also evidences reporting null effects on adiponectin (Brull et al, 2017; Hsu, Liao, Lin, Tsai, Huang, & Chou, 2011; Liu et al, 2014; Miyawaki et al, 2018) and/or leptin (Gholamrezayi et al, 2019; Jeong et al, 2020; Mirmiran, Hosseini, Hosseinpour‐Niazi, & Azizi, 2019). Similarly, evidence from meta‐analyses has remained inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained showed that after three weeks of administering the capsules of C. sinensis, there was a decrease in blood pressure and cholesterol. Unlike the previous study, Maeda-Yamamoto et al [41] evaluated the consumption of two types of green tea for twelve weeks to assess visual function and blood pressure. According to the data obtained, there was no decrease in blood pressure.…”
Section: Camellia Sinensis L Kuntzementioning
confidence: 99%